Index-Futures Lead-Lag And Price -Volume Causality: A Study Of The Malaysian Stock Index Futures Market - Ramasamy, Suganthi (2003)
Although much research has been undertaken on the index-futures lead-laq and price-volume causality in developed countries hardly has any been focused on the Malaysian stock index futures market. This study focuses on the index-futures lead-laq and price-volume causality in the Malaysian stock index futures market. This research is also intended to examine the seasonal effects in the Malaysian stock index futures market.